Pengaruh Kualitas Layanan Halal dan Citra Destinasi Wisata Halal terhadap Kepuasan Wisatawan Muslim - Ligery, Finny; Kusnoaji Nugroho, Didik; Saputra, Yusuf; Subandi, Subandi (CV. Creative Tugu Pena, 2022)
The research aims to determine the satisfaction of Muslim tourists which is thought to be influenced by the quality of halal services and the image of halal tourist destinations. This research was studied quantitatively with the unit of analysis being Muslim tourists in Metro City who had visited halal tourist destinations. Sampling was carried out using purposive sampling of 150 people and the data was processed using path analysis. The research results show that halal service quality (X1) has a positive and significant influence on the image of halal tourist destinations (X2) of 0.86. Halal service quality (X1) has a positive and significant influence on Muslim tourist satisfaction (Y) of 0.62. The image of a halal tourist destination (X2) does not have a positive influence on Muslim tourist satisfaction (Y). Keywords: Halal Service Quality, Image of Halal Tourism Destinations